Characterization and storage study of squash jam - Lozano, Sandra Jomillo (1997.)
Three different ratios of squash pulp to cocomilk were used to determine the most acceptable formulation of squash jam.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Squashes; Jam